Sebutlah Kami Tuli: Call Us Deaf - Hauschildt, Sean Ryan; Wijaya, Laura Lesmana; Budidharma, Cristophorus; Rodiah, Siti; Rachmat, Ariani; Muchlisin, Dafi (Advances in Social Sciences Research Journal, 2023)
Indonesia is an archipelagic nation consisting of diverse ethnicities and languages in southeast Asia. As in all nations, one of the linguistic communities found across the islands is made up of Deaf people. The limited research available about these Deaf Indonesians tends to focus on the linguistics of their language, BISINDO. However, almost nothing is known about their cultural traditions except studies about a Deaf Village in Bali. Currently, there are ongoing discussions among Deaf Indonesian communities in Java about Deaf identity. Most of these Deaf members espouse a cultural view of what it means to be Deaf. The argument centers on what is the correct term for a person who is deaf; one side of the argument is that Deaf people have a cultural identity, expressed as tuli (Deaf) while the other side maintains a medical view, expressed as tuna rungu (hearing impaired). These Indonesian Deaf perspectives are shared and documented for potential future research.